Optimal Placement and Sizing of TCSC using Gravitational Search Algorithm - Purwoharjono Purwoharjono; Muhammad Abdillah; Ontoseno Penangsang; Adi Soeprijanto (Institute of Advanced Engineering and Science, 2012)
This paper represents the GSA that can be used to determine the optimal location and rating of FACTS devices. They are devices used to regulate and improve the power flow in the power system. The method used in this study was GSA. FACTS types used were TCSC implemented on 500kV Java-Bali Power System. Load flow results before optimization showed that the active power loss was 297.607MW. While the load flow results after optimization using GSA with 5-TCSC obtained were 287.926MW of active power loss, with 10-TCSC, it was obtained 281.143MW of active power loss. In addition, using 15-TCSC, the active power loss obtained was 279.405MW. GSA methods can be used to minimize power losses and transmission lines as well as to improve the value of the voltage in the range of 0.95+ 1.05pu compared with load flow results before optimization. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1183